PEMANFAATAN TEPUNG TALAS DAN FORMULA TEMPE SEBAGAI BAHAN PEMBUAT COOKIES - Sitohang, Nur Asnah; Siregar, Farida Linda Sari (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Intake of nutritious foods is very important for pre schools in order to grow and develop optimally. One of the food sources of energy (non starch food) is the tuber of taro bogor. Bulbs taro bogor used as food industry materials can be processed into flour taro and made into various processed products such as dry bread, meatballs, and others. While as a source of vegetable protein from beans are soybeans that have been consumed by the community, among others, tempe, soy sauce, and others. Community service method used is education, training of cookie making based on taro flour and tempe formula, early detection and early intervention deviation of child growth and mentoring. This community service aims to empower the mother of pre school age in utilizing taro flour and tempe formula in order to develop food diversity and increase the appropriate knowledge and improve the nutritional status of children. This community service is done at Posyandu Klinik Bersalin Mawar Babar Sari and Posyandu Anggrek 1 Klinik Bersalin Marinta Ulina in Desa Baru, Pancur Batu ,Deli Serdang. The result of this dedication to the community is that mothers are able to make taro flour, tempe formula and process it into cookies well and increase the nutritional status of children. It is therefore advisable for the mother to be diligent in making cookies and making it an additional food for pre schools.Keywords: Cookies, Flour Taro, Formula Tempe, Nutritional Status, Pre school